Microscopic changes in the spinal extensor musculature in patients experiencing chronic spinal pain: protocol for a systematic review - Purushotham, Shilpa (BMJ Open, 2021)
INTRODUCTION: Chronic spinal pain (CSP) is the most common musculoskeletal disorder and is a leading cause of disability as per the Global Burden of Diseases. Previous reviews of microscopic changes in the spinal extensor muscles of people with CSP have focused on the lumbar region only and the results have been inconclusive. Therefore, in this protocol, we aim to assess microscopic changes in the extensor muscles of all spinal regions, investigating regionally specific changes in muscle fibre types of the spinal extensor muscles in patients with non-specific CSP. METHODS/ANALYSIS: This protocol was designed using Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guidelines. Searches will use the following databases: MEDLINE, Embase, PubMed, CINAHL Plus and Web of Science along with relevant grey literature searches. Two reviewers will conduct the searches, perform data extraction, apply inclusion criteria and conduct risk of bias assessment using Newcastle-Ottawa Scale. Data will be synthesised and analysed independently. If there is sufficient homogeneity, then meta-analysis will be conducted by the reviewers jointly. If not, meta-synthesis or narrative reporting will be performed. The quality of the evidence will be assessed using Grading of Recommendations, Assessment, Development and Evaluation (GRADE) guidelines. ETHICS AND DISSEMINATION: The results of this study will be submitted for publication to a peer-reviewed journal and will be presented at conferences. Ethical approval for this systematic review was not required due to no patient data being collated. PROSPERO REGISTRATION NUMBER: CRD42020198087.